Thailand’s higher education ESP practitioners: Problems, solutions and a potential practices model - Chaovanapricha, Traithana; Champakaew, Wilawan (Asian Journal of Education and Training, 2023)
A comprehensive needs analysis is crucial to guide the design and teaching of English for Specific Purposes (ESP) courses. However, a number of studies neglect certain elements of needs analysis, which can result in problems in subsequent stages of ESP teaching. This mixed-method study aimed to identify the problems that higher education ESP practitioners in Thailand encountered and the solutions they employed and to develop a potential practices model for ESP practitioners. Semi-structured interviews and Analytic Hierarchy Process (AHP) pairwise comparisons were employed to reveal 54 problems in six categories. Three highest-ranked problems were 1) the ESP practitioners’ lack of specialization in relevant fields (34.62%), 2) unsuitable classrooms and facilities (29.15%), and 3) the lack of specific course objective-oriented and cost-effective commercial textbooks (19.09%). The average consistency ratio (C.R.) was 0.32. The study suggested the need for training provisions and inclusion of ESP courses in English curricula. The ESP practices model suggested practices for institutions, such as conducting comprehensive needs analysis and providing suitable facilities and budgets. ESP practitioners were advised to utilize needs analysis for course design and employ active learning approaches. These recommendations aimed to enhance ESP education and improve an English curriculum, teaching practices, and evaluation processes.